3(1-6)=29-5n

Simple and best practice solution for 3(1-6)=29-5n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-6)=29-5n equation:



3(1-6)=29-5n
We move all terms to the left:
3(1-6)-(29-5n)=0
We add all the numbers together, and all the variables
-(-5n+29)+3(-5)=0
We add all the numbers together, and all the variables
-(-5n+29)-15=0
We get rid of parentheses
5n-29-15=0
We add all the numbers together, and all the variables
5n-44=0
We move all terms containing n to the left, all other terms to the right
5n=44
n=44/5
n=8+4/5

See similar equations:

| -11x-18=-95 | | x^2-8x-1520=0 | | 8/n+6=10/6 | | 3^3x+1=81^x+2 | | 5n*7=3n-1 | | 22a+96-13a=18-9a+8 | | 4x+2(6x+20)=8 | | x2+6x-40=0. | | (80-8x)/2=8x | | -9m-2=-7m-6 | | 41-2x+7x+5=360 | | x=48x+56 | | -85=-7+3(-6n+4) | | 41-2x+7x+5=180 | | 9x-53=5x+52 | | 5x-16=4x | | x=8(7x+6) | | 8x=(80-8x)/2 | | -105=-3(4n+7) | | 16(x/16)=16(7/10) | | 6x-200=17,700 | | x=8(13x) | | 8x-17)=(5x+52=180 | | 5(-5b+7)-1=-141 | | 13x+60+4x+93=90 | | 8x-17)=(5x+52 | | 13x+60+4x+93=180 | | x2+9999=23 | | -2m=-m+10 | | 13x+60=4x+93 | | 6x+200=17,700 | | 2(x-3)+3(x-1)=2x-3 |

Equations solver categories